Synthesis and evaluation of fluorinated tetrahydrocarbazoles as probes in NMR based binding assay of the E. coli β sliding clamp - Olsen, Cecilie Elisabeth; Simonsen, Signe; Merugu, Srinivas Reddy; Eigner, Vaclav; Aachmann, Finn L; Kragelund, Birthe B; Sundby, Eirik; Hoff, Bård Helge (Bioorganic & medicinal chemistry, 2025)
Bacterial β sliding clamp (β-clamp) is an emerging drug target currently lacking small-molecule inhibitors with good in vivo activity. Thus, there is a need for fast and simple screening methods for identifying inhibitor candidates. Here we demonstrate the use of nuclear magnetic resonance spectroscopy (NMR) for evaluating compound binding to the E. coli β-clamp. To identify suitable molecular probes, a series of tetrahydrocarbazoles were synthesized, some of which contain fluorine. Key challenges in the synthesis were formation of regioisomers during the Fischer indole reaction and reducing racemization at the stereogenic center. The tetrahydrocarbazoles were assayed against the E. coli β-clamp by saturation-transfer difference (STD) NMR, waterLOGSY and T1ρ. Analysis by isothermal titration calorimetry gave KD-values of 1.7-14 μM for three fluorinated probe candidates, and NMR chemical shift perturbation experiments confirmed these molecules to directly interact with the β-clamp binding pocket. Binding of the fluorinated molecules to β-clamp was easily observed with 19F-observed T2-based binding experiments, and proof of concept for a fluorine-based binding assay for E. coli β-clamp binders is provided.
Keywords: proteiny z Escherichia coli; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; halogenace; Molecular Probes; Protein Binding; Racemization; STD NMR; Escherichia coli; vazebná místa; magnetická rezonanční spektroskopie; Escherichia coli Proteins; Binding Sites; molekulární struktura; Molecular Structure; β sliding clamp; Carbazoles; Halogenation; vazba proteinů; Tetrahydrocarbazole; molekulární sondy; E. coli; Magnetic Resonance Spectroscopy; (19)F NMR displacement assay; karbazoly